Advanced Infrastructures for Future Healthcare - Marsh, Andy (IOS, 2013)
Healthcare is a major candidate for improvement in any vision of the kinds of "information highways" and "information societies" that are now being visualised. The (interactive) communication between healthcare providers and their patients or other healthcare providers regardless of geographic distance, namely telemedicine, will become of central importance. The objective of any advanced infrastructure that can be imagined for future healthcare must be to provide a global uniform level of healthcare. To facilitate the possibilities for any international collaboration standardised approaches must be adopted. This book has been mainly written for specialists, practitioners, scientists and managers in the new growing area of health information technologies. It is particularly relevant for those people - a large increasing number - who bridge and integrate knowledges in medicine (basic and clinical) and advanced technologies such as IT. The intended audience is broad and interdisciplinary; biomedical engineers, medical practitioners interested in the advanced IT infrastructures applied to medicine, computer scientists, academic professionals and graduate students, health care managers, standardization bodies, industrial engineers: designers and planners of innovative health care technologies, specialists in telemedicine, internet computing, computer graphics applications.